Family's functioning and adaptationin married couples with violation of family health and different women's addictive status - M. V. Savina (Kazimierz Wielki University, 2016)
Savina M. V. Family's functioning and adaptationin married couples with violation of family health and different women's addictive status. Journal of Education, Health and Sport. 2016;6(9):1004-1014. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.252806 http://ojs.ukw.edu.pl/index.php/johs/article/view/4183         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7                                                                                                                                      © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016.   UDC 616.89-008.48:616-055.2   FAMILY'S FUNCTIONING AND ADAPTATIONIN MARRIED COUPLES WITH VIOLATION OF FAMILY HEALTH AND DIFFERENT WOMEN'S ADDICTIVE STATUS   M. V. Savina   V. N. Karazin Kharkov National University, Ukraine psychotyp@gmail.com   Summary Objective - to study family functioning and adaptation in married couples with violation of family health and different women's addictive status, to identify further targets of psychocorrection. Contingent and methods. Through clinical psychological and psychodiagnostics methods, 371 married couple who applied for help from the violation of family relationships were examined. Among them 321 families, were manifestations of addictive behavior (AB) in women (IG1), while the other 50 families - normative indicators AB in women (IG2). As a comparison group (CG) examined 50 relatively harmonious families. Results. Married couples of CG demonstrated the success of family functioning and high adaptation with adapted type of marriage. For married couples of IG1 was inherent mutual assessment of family functioning of the breach at medium severity, and a moderate decrease in adaptation of the prevalence of inconsistent type of marriage. In contrast, married couples of IG2 established pathological congruence failure of both spouses functions related to violation of family functioning high-level expression, and a significant reduction in adapting to the formation of maladaptive type of marriage. We can assume that the AB, found in women from families with moderate marital conflict, middle-failure of family functions and inconsistent type of marriage, became a way of leveling emotional stress that arise due to non-receipt of family feeling shelter and psychological support, and reduced the level of severity. In contrast, women without AB, current negative psychoemotional frustration background implemented within the family, thus creating a higher level of marital conflict, causing high levels of destruction of family functioning and formation of maladaptive type of marriage. Conclusion. The data were assigned us a basis for developing the psychological treatment and support family health of women in AB. Key words: family's functioning, family's adaptation, women, addictive behavior, couple.